2016
DOI: 10.3109/10717544.2016.1157840
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic activity and stability enhancement of human insulin–tat mixture loaded in elastic anionic niosomes

Abstract: This study aimed to investigate the synergistic effect of trans-activator of transcription (Tat) and niosomes for the improvement of hypoglycemic activity of orally delivered human insulin. The elastic anionic niosomes composing of Tween 61/cholesterol/dicetyl phosphate/sodium cholate at 1:1:0.05:0.02 molar ratio loaded with insulin-Tat mixture (1:3 molar ratio) was prepared. Deformability of the elastic anionic niosomes decreased after loaded with the mixture of 1.35 times. For the in vitro release, the insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Dual delivery technologies that combine the beneficial properties of CPPs and NPs may improve oral INS delivery 12,13. Recently, several approaches to oral delivery of INS using CPPs/NPs have been developed, and a number of recent studies have demonstrated significant improvements in pharmacological availability (PA) following oral administration of INS using delivery systems such as nanoparticles,1418 nanocapsules,19 nanoemulsions,20 and liposomes,21 with PA values ranging from 11% to 17%. However, the hypoglycemic impacts observed in these studies were achieved using a relatively complicated chemical conjugation-based formulation with enteric-coated capsules 22.…”
Section: Introductionmentioning
confidence: 99%
“…Dual delivery technologies that combine the beneficial properties of CPPs and NPs may improve oral INS delivery 12,13. Recently, several approaches to oral delivery of INS using CPPs/NPs have been developed, and a number of recent studies have demonstrated significant improvements in pharmacological availability (PA) following oral administration of INS using delivery systems such as nanoparticles,1418 nanocapsules,19 nanoemulsions,20 and liposomes,21 with PA values ranging from 11% to 17%. However, the hypoglycemic impacts observed in these studies were achieved using a relatively complicated chemical conjugation-based formulation with enteric-coated capsules 22.…”
Section: Introductionmentioning
confidence: 99%